Purple Cleome (Cleome rutidosperma) Growth, Yield, and Total Flavonoid Under Different Media Compositions and Harvesting Frequencies - Dardiri, Dardiri; Aziz, Sandra Arifin; Melati , Maya (Journal of Tropical Crop Science, 2026)
Purple cleome (Cleome rutidosperma) is a medicinal plant known for its flavonoid content, which confers multiple pharmacological benefits. However, cultivation methods to optimize both biomass production and bioactive compound accumulation remain underdeveloped. This study aimed to assess the influence of planting media composition and harvesting frequency on the growth, yield, and total flavonoid concentration of purple cleome. The experiment was conducted in Gunung Batu, Bogor, Indonesia, from January to April 2025, employing a two-factor randomized block design. The first factor was planting media composition, with four treatments: 100% soil (0) and soil mixed with cow manure at ratios of 1:1, 1:2, and 1:3 (v/v). The second factor was harvesting frequency, with two levels: A single harvest at 8 weeks after planting (WAP) and two harvests at 4 and 8 WAP. Results indicated that all tested media compositions supported plant growth effectively. Notably, total flavonoid concentration was significantly higher at 4 WAP compared to 8 WAP. Moreover, cumulative flavonoid yield from two harvests was significantly greater, reaching 5,639.80 mg quercetin equivalents (QUE) per plant dry weight, compared to 1,456.50 mg QUE per plant from a single harvest. These findings suggest that harvesting at multiple intervals enhances flavonoid yield in purple cleome cultivation.